Gender aspect of triglyceride, HDL, and their ratio in high school teachers in Makassar City, Indonesia - Jafar, Nurhaedar; Hasan, Nurzakiah; Hadju, Veni; Thaha, Ridwan (Al-Sihah: The Public Health Science Journal, 2020)
Triglycerides, HDL, and their ratio are associated with metabolic disorders and diseases. Gender is known to have a relationship with these factors, but not consistent. This study wanted to see the relationship between gender and triglyceride levels, HDL levels, and the triglyceride / HDL ratio in secondary school teachers in Makassar City. The study was conducted with a cross-sectional approach in 6 junior high schools and 6 senior high schools with a total population of 200 teachers and involved 122 samples of teachers from secondary schools in Makassar City. Sampling using a stratified random sampling technique. The measurement of triglyceride and HDL levels was carried out by the Prodia laboratory. Data analysis was performed using the chi-square test. The results showed that there was a relationship between gender and triglyceride levels (p = 0.004). However, no relationship was found between HDL levels (p = 0.856) and the triglyceride / HDL ratio (p = 0.959) among secondary school teachers in Makassar City. Interventions to improve triglyceride levels must consider gender aspects primarily by paying more attention to male teachers.